Caracterização e classificação de solos em "ilhas florestais" e savanas associadas no Nordeste de Roraima - Feitosa, Keily Katiany Almeida (2009)
Knowledge of physical and chemical properties of soil under forest islands, embedded in savanna ecosystems is fundamental to its sustainable use and to understand its origin. This study aimed to identify the soil influence the occurrence of forest islands in Savannah. The study was conducted on four Islands Forestry (IF) and Savanna (S) adjacent, located in northeastern Roraima. Each Island Forest transects were established in the east - west and north - south, along which the trenches were opened in May. Since, for each class of land identified, was an open trench of 200 cm depth as modal. The other, 40 cm. These trenches were collected and undisturbed samples at depths from 00 to 10 cm, 10-20 cm and 20-40 cm. The soil samples were used to study the density of the soil, while disturbed samples for physical and chemical analysis. We established a transect bypassing each Island Forest (IF), a distance of 100 meters from the border, to minimize the effects of the transition. Along this transect, five trenches were opened halfway, and was employed the same method used to collect data on forest islands. Data were obtained from both physical and chemical environments. The data were selected and treated statistically by analysis of variance (ANOVA). Prevailed in the islands forest soils with colors red, yellow, yellow-red as prevailed in the savanna soil with burnished colors and yellow. The highest values of soil density and penetration resistance were observed in soils under savanna (S), while higher moisture values were found in Forest Islands (FI). For soil chemical properties were observed in the highest values of calcium, magnesium, potassium, phosphorus, total bases, cation exchange capacity, total effective cation exchange capacity, base saturation and organic matter in soils under forest, while the savannah showed higher concentrations of aluminum and aluminum saturation increased. The results indicated better physical and chemical conditions in soils under forest islands. The soils under (S) are undernourished while in the islands are eutrophic, with the exception of (IF1). As the organic matter content of the factor determining factor for the soil conditions of the islands. In this study, the dominant soil class in the study area was followed by Ultisols and Oxisols Plinthosols. The taxonomic classification to the first category level does not explain the occurrence of forest islands embedded in the savanna.